The Costs of Medical Care for Covid-19 Patients: A case study in Turkey - Cenk Teker; Dogancan Cavmak; Hakan Avci (ACHSM, 2021)
Objective: This study aims to calculate the medical costs of Covid-19 patients for hospitals based on the severity of clinical care. Design: The study was conducted in a hospital in Istanbul/Turkey. A micro-costing approach was performed using historical cost data for one year. All direct and indirect medical inputs were determined in quantities and monetary values for four types of Covid-19 patients in the hospital. Results: The analysis calculated the unit cost of an outpatient to be 459,99 ₺, while the cost per day for inpatient to be 1.184,63 ₺, for non-intubated in intensive care unit to be 1.938,11, for intubated in the intensive unit to be 2.393,99₺. The study also indicates that the total cost of a non-intubated patient in intensive care units is 1,54 times higher than the total cost per inpatient. An intubated patient's cost is 2,08 times higher than an inpatient's cost. Conclusion: This study indicates that Covid-19 patients incur significantly high costs for hospitals. The findings of the study provide empirical data for different types of patients which can be used in clinical management and can help all related governing bodies to plan their actions and make the decisions